Hydropeaking impact assessment for Iberian cyprinids and leuciscids: An adaptation of the hydropeaking tool method. (1st February 2022) - Godinho, Francisco N.; Alexandre, Carlos; Almeida, Pedro R.; Martínez‐Capel, Francisco; Cortes, Rui M. V.; Quintella, Bernardo R.; Sanz‐Ronda, Javier; Santos, José M.; Palau, Antoni; Pinheiro, António N.; Boavida, Isabel
Abstract: Hydropeaking negatively affects fish assemblages, but knowledge gaps still constrain our ability to rank and mitigate the impacts of different hydropower operation regimes at particular power plants. This is especially relevant for species and rivers for which the effects of hydropeaking are less investigated, such as the Iberian Cypriniformes and Mediterranean rivers. Recognizing the potential of the hydropeaking tool method (HT) developed for salmonids to systematically assess hydropeaking impacts, we adapted it for Iberian Cypriniformes. The general tool framework developed for the salmonids was kept for the Cypriniformes, with the combined use of factors describing the hydromorphological effects and factors related with fish vulnerability to assess hydropeaking impact. Effect and vulnerability factors were developed for Iberian cyprinids and leuciscids establishing preliminary thresholds for each indicator with three different levels of hydropeaking impact on the targeted taxa. The proposed factors and thresholds were critically reviewed and ranked by experts on Iberian Cypriniformes ecology and Mediterranean rivers functioning. Overall, the timing and distribution of peaking events were ranked higher by the experts in the effect factors, whereas the population size of barbel and smaller native Cypriniformes, as well as the degree of limitations in recruitment, were ranked higher in the vulnerability factors. Although there was some divergence in the expert opinions, a final set of effect and vulnerability factors was established, that retained most of the ones proposed for the salmonids, but included new ones, particularly for vulnerability. The present study provided a comprehensive, straightforward, and systematic assessment tool for evaluating hydropeaking impacts on Iberian Cypriniformes.